The way students of STIKes Yarsi Mataram over come dysmenorrhea - Setyawati, Irni; Utami, Kusniyati; Riezqy Ariendha, Dian Soekmawaty (Journal of Fundus, 2021)
Approximately 50% of women aged 15-24 years who experience menstruation experience dysmenorrhea pain, but young women often do not know how to deal with it. Primary dysmenorrhea occurs within the first year or two of menstruation. Primary dysmenorrhea can be treated by using drugs to reduce pain or compressing the stomach with a bottle filled with hot water, and even exercising (Andrews, 2010). STIKes Yarsi Mataram students have been equipped with knowledge about dysmenorrhea, but not all students apply it in their daily life. Based on the foregoing, it is necessary to know how female students deal with dysmenorrhea in their daily lives. This study used a descriptive design with a cross-sectional approach. The population in this study were all active students in semesters 2 and 4 who were female in the diploma 3 midwifery and nursing study program for the 2018/2019 academic year. The sampling technique used a total population sampling with a total of 106 people. Data were analyzed by univariate. Most of the respondents experienced dysmenorrhea during menstruation by 88.7% and how to deal with pain by sleeping on your side was mostly done by respondents (48.1%). This is followed by prostration, doing nothing, taking medicine and warm compresses. It is hoped that there will be counseling, information and education about the intensive treatment of dysmenorrhea by lecturers to female students.